2011
DOI: 10.1037/a0022205
|View full text |Cite
|
Sign up to set email alerts
|

Age-related associative deficits are absent with nonwords.

Abstract: Words and nonwords were used as stimuli to assess item and associative recognition memory performance in young and older adults. Participants were presented with pairs of items and then tested on both item memory (old/new items) and associative memory (intact/recombined pairs).For words, older participants performed worse than young on item and associative tests but to a greater extent on the latter. In contrast, for nonwords, older participants performed equally worse than young on item and associative tests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Our main prediction, that the age-related associative deficit would be alleviated with high-(relative to low-) frequency words, was not supported by the current data. Note that an earlier study found the same when comparing words with nonwords (Badham & Maylor, 2011). Recent research from our laboratory indicates that age differences in the use of prior knowledge depend on the experimental paradigm and this is explored further in the General Discussion in the context of both Experiments 1 and 2.…”
Section: Discussionmentioning
confidence: 73%
“…Our main prediction, that the age-related associative deficit would be alleviated with high-(relative to low-) frequency words, was not supported by the current data. Note that an earlier study found the same when comparing words with nonwords (Badham & Maylor, 2011). Recent research from our laboratory indicates that age differences in the use of prior knowledge depend on the experimental paradigm and this is explored further in the General Discussion in the context of both Experiments 1 and 2.…”
Section: Discussionmentioning
confidence: 73%
“…All nonwords had no orthographic neighbors, five to seven letters, no more than two syllables, and had high probability of being correctly identified as a nonword in a lexical decision task (probability range = 0.97 to 1). Nonwords have been used previously as items within associative recognition tasks (Badham & Naylor, 2011; Naveh-Benjamin, 2000). In general, associative recognition tasks can improve with extensive practice (hundreds of trials) (Kray & Eppinger, 2006; Rogers & Fisk, 1991; Wexler et al, 1997) and have been shown to activate brain regions within the hippocampus, striatum, frontal cortex, and anterior cingulated areas (Holcomb, 2004; Kumaran & Maguire, 2007; Meltzer & Constable, 2005; Simon, Vaidya, Howard, & Howard, 2011; Wheeler, McAndrews, Sheard, & Rovet, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Research has revealed an age-specific impairment for recognition memory of pairs of words and other stimuli [15]. Older adults have greater difficulty remembering associations between components of information (e.g., a person’s face and name) than individual components (e.g., a person’s face, a person’s name; [6]).…”
Section: Introductionmentioning
confidence: 99%
“…Age differences in encoding strategies might explain age differences in associative memory but why do older adults often perform equivalently to younger adults on the item task? To explain this age by test-type interaction effect, researchers have suggested that existing knowledge may be especially helpful to older adults on the item test, boosting their performance above that on the associative task through the creation of new concepts and/or mediators [1, 1517]. Compared to college-aged students, older adults are likely to have a larger assortment of experiences and knowledge that can support performance in a single-item recognition task [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation